Revisionary notes on the genus Diplonevra Lioy (Diptera: Phoridae) and a new key to species from China - Liu, Guang-Chun; Disney, R. Henry L. (Zootaxa, 2024)
The Chinese species of Diplonevra are reviewed; two new species, D. pilisparsa sp. nov. and D. nudisetalis sp. nov. are described; D. biflagella Lee et al. is synonymized with D. taigaensis Michailovskaya; a revised key to Chinese species based on males is presented.